Energy Efficient Multi-Path Routing in MANET’s Using Swapping of Nodes and by Load Balancing of Data Packets on to the Nodes - Prof. Kirti Wanjale, Ms. Vrushabha J Muramkar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To conduct multiple routes in a mobile Ad-hoc network (MANET) in order to balance the load onto nodes and make nodes more energy efficient. As the battery life of a node rises, swapping of nodes is done to make the network more dependable. In this case, the best fit function will be utilized to exchange two totally suitable nodes. Initially, the system develops a self-configuring network with mobile nodes and no fixed infrastructure. After constructing the network, a multi-path source and destination are chosen for data transmission. After that, a multi-path is discovered for transferring the data, and the shortest way is determined based on node energy and distance. After that, the energy consumption of each node is determined, the node with the lowest energy level is exchanged with the node with the highest energy level using the swapping algorithm, and data is sent to the destination node. The battery usage increases as the load on the destination node increases. Priority sequencing should be used for data cluster formation in order to minimize node battery failure and excessive energy usage.